THE THE PRINCIPAL'S STRATEGY IN IMPROVING THE QUALITY OF EDUCATION UNITS BASED ON DISCIPLINE AND CHARACTER AT SDN LHOK RUKAM, TAPAKTUAN, ACEH SELATAN : PRINCIPAL'S STRATEGY IN IMPROVING THE QUALITY OF EDUCATION UNITS BASED ON DISCIPLINE AND CHARACTER AT SDN LHOK RUKAM, TAPAKTUAN, ACEH SELATAN - hasrinaldi hasrinaldi (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
Improving the quality of education is a top priority in managing educational institutions, particularly at the elementary school level. This study focuses on the strategies employed by the principal of SDN Lhok Rukam, Tapaktuan, Aceh Selatan, to enhance education quality through the integration of discipline and character values. A qualitative case study approach was utilized, with data collected through in-depth interviews, direct observations, and document analysis. The findings reveal that the principal plays a central role in planning and implementing discipline- and character-based strategies. These strategies include establishing internal school policies, organizing teacher training programs to enhance pedagogical competence, and engaging parents in the educational process. The integration of discipline and character values is embedded in teaching and learning activities, both inside and outside the classroom. This integration has had a positive impact on various aspects, including increased student engagement in learning, the development of a positive school culture, and improvements in both academic and non-academic achievements. Moreover, it fosters strong character traits in students, such as responsibility, teamwork, and respect for others. However, the study also identifies challenges in implementing these strategies, including limited resources, insufficient active participation from some parents, and resistance to change among certain teachers. To address these challenges, the principal adopts a collaborative approach and provides recognition to stakeholders who support the initiatives.